Environmental Management and Monitoring Efforts in Achieving Sustainable Development at PT Japfa Comfeed Indonesia - Rozi, Fahrur; Husin, Sukanda; Rembrandt, Rembrandt (International Journal Labs, 2022)
Background: Efforts to manage the environment for business purposes through the presence of companies manufactured large-scale have a major impact on the environment, pollution, and various environmental damage are unavoidable consequences, but through environmental monitoring and management efforts, the negative impacts of environmental management can be minimized. Aim: This paper aims to review environmental management and monitoring efforts in achieving sustainable development at PT Japfa Comfeed Indonesia. Method: This study uses a normative juridical approach, where this study looks at the application of existing laws and theories with the reality in the field. The data were collected in the form of primary data obtained from the PT. Japfa Comfeed Indonesia, Tbk Padang Branch Office related to the implementation of environmental management efforts and environmental monitoring efforts, as well as secondary data obtained from primary, secondary, and tertiary legal materials. Findings: The results of this study showed that environmental management efforts and environmental monitoring efforts have a role as a reference and guideline for PT. Japfa Comfeed Indonesia, Tbk Padang Branch Office in carrying out company activities and environmental management, becomes a reference and guideline for the government and the community regarding the impacts or problems that will arise from the production activities of PT. Japfa Comfeed Indonesia, Tbk.